EVALUATION OF THE EFFECT OF FERROUS SULFATE ON ENAMEL DEMINERALIZATION OF HUMAN DECIDUOUS TEETH: AN IN VITRO STUDY (Journal of Dentistry & Public Health (inactive / archive only), 2017)
Objective: This study aimed to evaluate the effect of ferrous sulfate (FS) on demineralized and non-demineralized human deciduous teeth. Additionally, it was evaluated the penetration extent of FS and its remineralizing effect on the enamel of deciduous teeth using Polarized Light Microscopy (PLM). Method: The sample comprised 44 human deciduous teeth. The 44 crowns were divided randomly into four groups: group A (FS after demineralization), group B (FS without demineralization), group C (only demineralization), and group D (control group). FS at 0.45 mol/L-1 was used daily (15 days) and demineralization was done by pH cycling (7 days). Then, three longitudinal slices of the crowns were photographed using PLM. The degree of penetration of the lesion or stain was measured in micrometers, as well as the distance between the external enamel surface and the core of lesion. Results: Group A showed a dark stain on the outer surface of enamel larger than the group B. It is suggested, a remineralizing effect when comparing groups, A and C. The mean depth and standard deviation for groups A, B, and C were 4.27µm (±1.49), 3.72 µm (±1.68) and 5.00 µm (±1.84), respectively. No dark stains were observed in group D. Conclusion: FS stained the demineralized and non-demineralized human deciduous teeth. However, dark stains in the non-demineralized teeth were smaller or absent, than in the demineralized teeth. Therefore, FS may have a protective effect against demineralization.